2021
DOI: 10.1186/s12864-021-07869-8
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomal dissection of soybean circadian rhythmicity in two geographically, phenotypically and genetically distinct cultivars

Abstract: Background In soybean, some circadian clock genes have been identified as loci for maturity traits. However, the effects of these genes on soybean circadian rhythmicity and their impacts on maturity are unclear. Results We used two geographically, phenotypically and genetically distinct cultivars, conventional juvenile Zhonghuang 24 (with functional J/GmELF3a, a homolog of the circadian clock indispensable component EARLY FLOWERING 3) and long juve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 63 publications
0
1
0
Order By: Relevance
“…Circadian clock together with light signals have gating effects on the expression of downstream genes at transcriptional and post-transcriptional levels, resulting in altered growth status under different photoperiods [9]. Many evidences in crop plants suggested that modulating the components of circadian clock pathway is an effective way to enhance the local adaption and abiotic resistance, thus enhancing agricultural productivity [10][11][12][13][14].…”
mentioning
confidence: 99%
“…Circadian clock together with light signals have gating effects on the expression of downstream genes at transcriptional and post-transcriptional levels, resulting in altered growth status under different photoperiods [9]. Many evidences in crop plants suggested that modulating the components of circadian clock pathway is an effective way to enhance the local adaption and abiotic resistance, thus enhancing agricultural productivity [10][11][12][13][14].…”
mentioning
confidence: 99%